English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Find a value for x such that 3+x, 4+x, and 5+x are consecutive terms in a geometric sequence.
I did (5+x)/(4+x)=(4+x)/(3+x) to get x, but the x's all cancel out.
Let me know what I'm doing wrong?

2007-04-02 12:56:50 · 6 answers · asked by ilovethechub 2 in Science & Mathematics Mathematics

6 answers

(5+x)/(4+x)=(4+x)/(3+x) is correct.

Do cross multiplication:
15+8x+x^2 = 16+8x+x^2
which leads to 15 = 16

Therefore, there is no solution.

2007-04-02 13:04:35 · answer #1 · answered by sahsjing 7 · 0 0

A geometric sequence is a sequence that has a common ratio (r). For this to be a geometric sequence (t2)/(t1) = r and (t3)/(t2) = r. Therefore, (t2)/(t1) = (t3)/(t2). We can plug the terms into this equation now to solve for x (t1 = 3+x; t2 = 4+x; t3 = 5+x).

(4+x)/(3+x) = (5+x)/(4+x) "cross multiply"
(4+x)(4+x) = (5+x)(3+x) "expand and simplify"
16 +8x +x^2 = 15 + 8x + x^2 "group like terms"
16 = 15 therefore no solution

This is an arithmetic sequence since these consecutive integers have a common difference of one and no common ratio.

2007-04-02 13:23:02 · answer #2 · answered by erkbergles 3 · 0 0

No matter what value you set x equal to, x+3, x+4, and x+5 will be consecutive integers. The common difference is the constant 1, and therfore the numbers are part of an arithmetic sequence. The reason your x's cancel out is that the problem has no solution.

2007-04-02 13:09:16 · answer #3 · answered by ironduke8159 7 · 0 0

You didn't do anything wrong. The x's cancel leaving 16 = 15. That means there is no solution. So the answer is that no such geometric sequence exists.

2007-04-02 13:04:41 · answer #4 · answered by hayharbr 7 · 0 0

using

an = a1 * r^(n - 1)

a2 = (3 + x) * r^(2 - 1)
4 + x = (3 + x)r
r = (4 + x)/(3 + x)

a3 = (3 + x) * r^(3 - 1)
5 + x = (3 + x) * r^2
(5 + x)/(3 + x) = r^2
r = sqrt((5 + x)/(3 + x))
r = (sqrt((5 + x)(3 + x)))/(3 + x)

(4 + x)/(3 + x) = sqrt((5 + x)(3 + x))/(3 + x)

4 + x = sqrt((5 + x)(3 + x))

(4 + x)^2 = (5 + x)(3 + x)

(4 + x)(4 + x) = 15 + 5x + 3x + x^2
16 + 4x + 4x + x^2 = 15 + 8x + x^2
16 + 8x + x^2 = 15 + 8x + x^2
16 = 15

Something isn't working out right.

2007-04-02 13:57:05 · answer #5 · answered by Sherman81 6 · 0 0

x-3 ,. x+ 3 ,., 3x- 3 are in G.P. then ( x+3)^3 = (x-3) ( 3x- 3) [ a,b,,c are G.P. then b^2 = ac ] x^2 + 6x + 9 = 3x^2 - 3x -9x + 9 or2x^2 =18x or x= 0 & x=9 so G.P.is -3 . 3 ,-3---------- and G.P. is --------- 6, 12, 24------------- answer [ a= 6 & r =2 ]

2016-11-25 21:45:03 · answer #6 · answered by ? 4 · 0 0

fedest.com, questions and answers